2017
DOI: 10.3390/ijerph14070821
|View full text |Cite
|
Sign up to set email alerts
|

Patterns Associated with Adult Mandibular Fractures in Southern Taiwan—A Cross-Sectional Retrospective Study

Abstract: Purpose: This study aimed to determine the patterns associated with adult mandibular fractures from a Level-I trauma center in southern Taiwan. Methods: The data of adult trauma patients admitted between 1 January 2009 and 31 December 2014 were retrieved from the Trauma Registry System and retrospectively reviewed. Fracture site and cause of injury were categorized into groups for comparison, and corresponding odds ratios (ORs) and 95% confidence intervals (CIs) were obtained by multivariate logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…According to the preliminary results of the present study, the frequency of injury was higher in men than that in women, and the mean age of the participants was 29.79±14.21 yr old. This is consistent with other studies' results [21][22][23] . Since the second and third decades of age are the most active period of human life 24,25 , and men have more work activities at the communities, and because of the major etiology of fractures and moods of men for risk-taking, these results are expected [26][27][28] .…”
Section: Discussionsupporting
confidence: 94%
“…According to the preliminary results of the present study, the frequency of injury was higher in men than that in women, and the mean age of the participants was 29.79±14.21 yr old. This is consistent with other studies' results [21][22][23] . Since the second and third decades of age are the most active period of human life 24,25 , and men have more work activities at the communities, and because of the major etiology of fractures and moods of men for risk-taking, these results are expected [26][27][28] .…”
Section: Discussionsupporting
confidence: 94%
“… 6 Road traffic accidents (RTAs) were a common cause in Taiwan, 3 especially motorcycle accidents; and it was shown that the condylar neck and head were the most common sites (32.0%), followed by the parasymphysis (21.7%) and symphysis (19.5%). 7 …”
Section: Introductionmentioning
confidence: 99%
“…While a cross-sectional retrospective study conducted at Southern Taiwan revealed that condylar neck and head were the most common sites (32%) followed by the parasymphysis (21.7%), symphysis (19.5%), angle and ramus (17.5%) and body (9.3%). (15) In an epidemiological survey of mandibular fractures in Caracas (Venezuela) evaluated the incidence and its combination patterns showed that the parasymphysis region was the most common location of mandibular fractures with 144 (27.6%) fractures. 16A road traffic accident was the major cause of trauma i.e.…”
Section: Figure 3: Yearly Distribution Of Etiology Of Mandibular Fracmentioning
confidence: 99%